Peningkatan Hasil Belajar Lempar Turbo Dengan Modifikasi Media Belajar Untuk Siswa Kelas IV Sekolah Dasar - Gunawan, Gunawan; Suhairi, Muhammad; Porja Daryanto, Zusyah (Indonesian Journal of Physical Education and Sport Science, 2022)
The purpose of this study was to obtain data on planning, implementation, and results of students' abilities in understanding turbo throwing lessons through modification of learning tools. The research method used in this research is descriptive method with the form of Classroom Action Research. The subjects of this study were fourth grade students, totaling 32 students. The technique used in this research is observation and test technique. Based on the research that has been done in the first cycle, there was an increase in student learning outcomes which previously only 15 students completed (47%) with an average score of 67.32 to 21 students who completed (66%) with an average score 76.43. This still has not reached the minimum completeness criteria, which is 70% of the number of students studied. Therefore, the researcher re-conducted classroom action research in the second cycle. Student learning outcomes in the second cycle further increased to 88% with the number of students who got a complete score of 28 people with an average score of 82.03. Based on the explanation, it can be concluded that the improvement of Turbo Throwing Learning Outcomes with Modified Learning Media has succeeded in achieving the minimum learning completeness criteria for fourth graders at State Elementary School 04 Pontianak East.